College Enrollment and STEM Major Choice in a Rural State: A Statewide Examination of Recent High School Cohorts - Tran, Que N.; Meyerink, Monte; Aylward, Alexandra; Luo, Fenqjen (Theory & Practice in Rural Education, 2021)
Rural students account for almost 20% of the US K-12 students, but rural context varies from state to state. This study uses a statewide longitudinal sample (N = 3,119) to analyze college enrollment and STEM major choice patterns of Montana’s public high school students in the academic years of 2013-2017. The binary logistic regressions showed that Montanan students are more likely to enroll into a 4-year institution than a 2-year institution. Also, students enrolled at a 4-year institution are more likely to consider STEM majors than students at a 2-year institution. Although high school GPA and ACT STEM scores are strong predictors for both college enrollment and STEM major choice, findings for race/ethnicity, gender, and free or reduced-price lunch status varied across the two outcomes. Specifically, race/ethnicity contributes to variation in college enrollment, but not STEM major choice. Similarly, free or reduced-price lunch status in high school is predictive of college enrollment, but not for STEM major choice. Although there was no difference in college enrollment type for gender, male students are more likely to select a STEM major, and this trend occurs at a rate of three times higher at a 4-year institution versus a 2-year institution. Our findings provide additional nuances of rural students, contributing to the understanding of their college enrollment and STEM major choices in the context of Montana - a large geographic, low populous state - which has received less attention than urban and high-density states.